DETERMINAN MINAT INVESTASI MAHASISWA DI YOGYAKARTA - Kintami Kintami; Yola Andesta Valenty (LPPM STIE Muhammadiah Bandung, 2026)
This study aims to determine the influence of investment knowledge, influencers, subjective norms, herding behavior, perceived behavioral control, and risk perception on investor interest among Yogyakarta students. The study population included 604,611 students. Sample size was determined based on the Slovin formula with a 10% error rate. The sampling technique used non-probability sampling with a convenience sampling method. The respondent criteria were students currently studying in Yogyakarta, aged between 18 and 25 years. A sample of 144 students was obtained through a questionnaire distributed using Google Forms. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) techniques with the help of SmartPLS software version 3.0. The research findings revealed that all variables met the validity and reliability test criteria, and all research hypotheses were accepted. The independent variables had a significant positive impact and had an explanatory power of 52.3% on the variation in student investment interest, as indicated by the R Square value of 0.523. The remaining 47.7% was contributed by other variables outside the study.